An exploration of Cleo’s loneliness in Coco Mellors’ Cleopatra and Frankenstein (2022) by using new criticism - Purwanto, Nisa Rahmayanti (Pioneer: Journal of Language and Literature, 2025)
This study explores Cleo’s loneliness in Coco Mellors’s Cleopatra and Frankenstein using a qualitative method. Although previous studies have examined loneliness in literary works, limited attention has been given to loneliness as an internal emotional condition that affects the dynamics of intimate relationships through the New Criticism approach. By using close reading, the analysis focuses on formal elements, namely characterization, plot, setting, symbol, and irony. Through this approach, the study reveals how Cleo’s loneliness is not a simply passing, but a condition that repeatedly shapes her decision, relationships, and sense of self. From moving, marrying, to hurting others, Cleo repeatedly attempts to escape from her loneliness. Rather than finding comfort from external connections, this study shows that Cleo finds emotional healing from within by returning to her artistic practice and transforming her pain into her art.